Managing ‘Ordinary Heritage’ in Poland: Łódź and Its Post-Industrial Legacy - Pielesiak, Iwona (European Spatial Research and Policy, 2015)
It could be argued that cultural heritage in Poland, like in other post-socialist countries, is losing its importance due to modernisation, and that its preservation is in conflict with new investment. The situation is caused by several factors. Firstly, free use of private property is often more valued than the care for historical landscapes, which could be attributed to the consequences of the economic crisis. Secondly, there are legal shortcomings in spatial planning and heritage conservation systems. Thirdly, cooperation among politicians, urban planners and heritage protection officers is not efficient. Since the transition period of the 1990s, historic relics have been exposed to multiple threats. The following case study of Łódź illustrates the general need for a change of approach towards cultural legacy management, especially in reference to more common heritage elements which are not under hard protection.